RISKS IN THE IMPLEMENTATION OF SMART TECHNOLOGIES IN URBANENVIRONMENTS - Chipriyanov, Mihail (E-Journal VFU, 2025)
Within the scope of the present study, a comprehensive and critical analysisis conducted on the main risks arising from the implementation of smart technologies in urbanenvironments, focusing on challenges to cybersecurity, financial sustainability, socialadaptation, and regulatory adequacy. Key issues identified include the vulnerability of IoTdevices, the financial burden of implementation, the digital divide, and the lack of unified legalframeworks. As a result of the analysis, specific strategies for minimizing these risks are935formulated, encompassing public-private partnerships, financial innovations, enhancement ofdigital literacy, and the creation of adaptive regulatory approaches. The conclusion drawn isthat the successful development of smart cities is directly dependent on the holistic managementof these multifaceted risks.
Keywords: Smart cities; Cybersecurity; Financial risks; Social challenges; Regulatory frameworks